Urodynamic evaluation of pelvic organ prolapse: women with and without urinary incontinence - Ghanbari Z (Tehran University Medical Journal, 2009)
"n Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0in 5.4pt 0in 5.4pt; mso-para-margin:0in; mso-para-margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:Arial; mso-bidi-theme-font:minor-bidi;} Background: Pelvic Organ Prolapse (POP) and related urinary symptoms are frequent disorders in elderly women and their management improves life expectancy and quality of life. Urodynamic tests applied in pathophysiologic diagnosis and treatment of urinary disorders are not always cost effective. This study aims to evaluate the results of Urodynamic tests in patients with pelvic organ prolaps."n"nMethods: This case- control study was done using UDI-6 questionnaire during 18 months in vali-e-asr clinic of Imam Khomeini Hospital, Iran with 105 cases of POP; the cases were divided into two groups: group one (66 cases with urinary incontinency) and group two (39 without incontinency) and assessed with urodynamic tests."n"nResults: Based on UDI-6, the patients of group one had more clinical symptoms (frequency, urine leakage, urge incontinence and stress incontinence). (p<0.001). Except for first desire to voide and normal voided volume indices, there were no significant differences in the other urodynamic parameters in two groups. Sensitivity and specificity of urgency leak in group one was 22 and 68/8% and in group two was 30 and 65/5% respectively. Stress leak sensitivity and specificity in group one were 25/4% and 100% and in group two were 57/1% and 71/9% respectively."n"nConclusion: In this study, considering sensitivity and specificity of symptoms and urodynamic test for urinary incontinency assessment is advised in patients with POP who need surgery.